Akselerasi Digital Literacy sebagai Upaya Peningkatan Kompetensi Profesional bagi Guru SD di Kabupaten Brebes - Rio Rizkiansyah; Asep Purwo Yudi Utomo; Rustono Rustono; Haryadi Haryadi; Audya Nilam Nariswari; Allamanda Kusumaning Anjora (Pelayanan Unggulan : Jurnal Pengabdian Masyarakat Terapan, 2025)
Digital literacy is a crucial competency for teachers. Accelerating digital literacy for elementary school teachers is not only about mastering digital tools and applications, but also about changing mindsets and approaches to teaching. There are three impacts for teachers and students if teachers are unable to master digital competencies: 1) teachers are less able to keep up with the latest technological developments; 2) teachers are unable to filter and process the latest information, resulting in a tendency towards misinformation; 3) students are less able to absorb the latest information and thus misuse the wrong sources of information. Given these impacts, training and mentoring are needed for elementary school teachers in Songgom District to acquire the right digital skills so that elementary school teachers can maximize their potential. Elementary school teachers in Brebes Regency still do not have good digital competencies. If left unchecked, more and more teachers will lack digital competency. This can lead to a lack of technology-related information that students can use to support their learning. Furthermore, inadequate technology skills can hinder differentiated learning within the independent curriculum. The Community Service Program, initiated by professors and lecturers with expertise in digital literacy and language, is highly relevant to the needs of teachers in Brebes Regency. Elementary school teachers are developing digital competencies by implementing interactive quiz-based learning and Canva-based learning media. These competencies can be applied by teachers in the classroom. Students are expected to absorb the material more meaningfully. Learning through the application of digital literacy by teachers will increase student interest and engagement in learning the material.